Sexual Symmetry : Love in the Ancient Novel and Related Genres. - Konstan, David (Princeton University Press, 2014)
""In the Greek romances, "" writes David Konstan, ""sighs, tears, and suicide attempts are as characteristic of the male as of the female in distress; ruses, disguises, and outright violence in defense of one's chastity are as much the part of the female as of the male."" Exploring how erotic love is represented in ancient amatory literature, Konstan points to the symmetry in the passion of the hero and heroine as a unique feature of the Greek novel: they fall mutually in love, they are of approximately the same age and social class, and their reciprocal attachment ends in marriage. He shows.
Cover; Contents.
Keywords: Classical fiction -- History and criticism.; Romance fiction, Greek -- History and criticism.; Romance fiction, Latin -- History and criticism.; Literary form -- History -- To 1500.; Fiction -- Classical influences.; Sex in literature.; Roman ancien -- Histoire et critique.; Roman -- Influence ancienne.; Sexualité dans la littérature.; HISTORY -- Ancient -- General.; Classical fiction; Fiction -- Classical influences; Literary form; Romance fiction, Greek; Romance fiction, Latin; Sex in literature; To 1500; Criticism, interpretation, etc.; History